The convergence of industrial and workers compensation laws in the 1990s in Western Australia - Guthrie, Robert (Curtin University, 2003)
This dissertation describes and interprets the effects of the significant changes to the workers compensation, industrial and related laws that occurred in the early 1990s in Western Australia. These could be characterised as motivated by a desire by the then Coalition Government to reduce access to legal representation in compensation claims, limit the potential of workers to claim damages for negligence and reduce the use of collective bargaining mechanisms to resolve industrial disputes. Arguably, the common philosophical themes were to individualise the relationship between employer and employee and to reduce the bargaining strength of workers. In general terms, these themes were presented under the guise of flexible workplace relations. Whether these outcomes were achieved is not the subject of this analysis, rather, the aim is to show that one (perhaps unintended) consequence of the legislative changes of the early 1990s was to create significant areas of overlap in various employment related laws. These areas of overlap have led to some difficulties within the various tribunals involved in the resolution of employment related disputes. Over the last decade, the issues arising from the 1990s amendments have crystallized into important principles, which are discussed in this work. The thesis of this dissertation is that an examination of the development of the industrial and workers compensation laws in Western Australia in the 1990s establishes sufficient commonality between the industrial relations and compensation systems to warrant the rationalisation of these two jurisdictions.